Rhetoric Demystified - MEDJEOUB, Rima (Journal of Human Sciences, 2019)
Since its inception by the Greek scholars up until the contemporary times,the termrhetorichas undertaken a plethora of meanings. Those meanings have mainly been associated with what caused its flourishment in the Greek and Roman periods, decay in the middle and early modern ages, and revival in the twentieth century via various rhetorical theories. No doubt, the novice researchers in the field would get confused by the wide array of denotations this term carries. Therefore, the current article deals the definitional and historical debate vis-à-vis the extension of the term rhetoric. It, besides, provides an explanation of the two phrases: rhetorical analysis and rhetorical criticism.